Modulation of Methamphetamine-Related Attention Bias by Intermittent Theta-Burst Stimulation on Left Dorsolateral Prefrontal Cortex - Chen, Tianzhen; Su, Hang; Wang, Lihui; Li, Xiaotong; Wu, Qianying; Zhong, Na; Du, Jiang; Meng, Yiran; Duan, Chunmei; Zhang, Congbin; Shi, Wen; Xu, Ding; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Previous studies have identified the treatment effect of repetitive transcranial magnetic stimulation (rTMS) on cravings of patients with methamphetamine use disorder (MUD). However, the mechanism underlying the treatment effect remains largely unknown. A potential candidate mechanism could be that rTMS over the dorsolateral prefrontal cortex (DLPFC) modulates the attention bias to methamphetamine-related cues. The purpose of this study is therefore to determine the modulation of rTMS on methamphetamine-related attention bias and the corresponding electrophysiological changes. Methods: Forty-nine patients with severe MUD were included for analysis. The subjects were randomized to receive the active intermittent theta-burst stimulation (iTBS) or sham iTBS targeting DLPFC for 20 sessions. Participants performed the Addiction Stroop Task before and after the treatment while being recorded by 64-channel electroencephalogram. Baseline characteristics were collected through the Addiction Severity Index. Results: Post-treatment evaluations showed a reduced error rate in discriminating the color of methamphetamine words in the active iTBS group compared with the sham iTBS group. Following rTMS treatment, we found decreased N1 amplitude (methamphetamine words > neutral words) on fronto-central electrodes and decreased P3 latency (methamphetamine words > neutral words) on parietal electrodes in active group. The change of N1 amplitude was positively correlated with cravings in active group. Moreover, reduced power of neural oscillation in beta band, manifesting at frontal central areas, was also found in active group. Conclusion: This study suggests that attention bias and electroencephalogram features during the attentional processing of methamphetamine words in methamphetamine patients could be modulated by iTBS applied to left DLPFC.